Meningkatkan Pengetahuan Siswa Dalam Penyelenggaraan Pameran Seni Rupa Melalui Metode Demonstrasi Di Kelas XI MIPA 5 SMAN 1 Muaro Jambi - Emriyasmen (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract: The primary purpose of this study is to improvestudents‟ knowledge in planning, actuating, and reporting of artexhibition for students in class XI MIPA5 SMAN 1 Muaro Jambi. Thisstudy employs the classroom action research in two cycles withdemonstration methods. Based on the study, student‟s knowledge inplanning, actuating, and reporting of art exhibition increases in eachcycle and raises the limit points determined.